2017
DOI: 10.24041/ejmr2017.45
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Natural Products on Body Weight and Biochemical Parameters in Healthy Rats

Abstract: The present study was undertaken to evaluate effect of natural products i.e. Anthocephalus indicus; KADAM, roots, Hibiscus rosa sinensis roots, Tinospora cordifolia stem and Cassia tora seeds in normal healthy rats. In this study ethanol extract of above mentioned medicinal plants had macerated with aqueous gum acacia (2%, w/v) suspension and fed orally (500 mg/kg bw p.o.) to male adult healthy normal rats of Charles Foster strain for 30 days. Results of this study showing that alcoholic extracts caused no any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Tehran first demonstrated elevation of minor hemoglobin in diabetes mellitus introduced the column method of separating out the fast hemoglobin, pointed out that HbA 1 C is related to control of diabetes. The advantages of Gly Hb estimation are those of a simple procedure, lack of any need for dietary preparation or for fasting, elimination of the variability usually found an oral glucose tolerance tests as well as an accurate reflection of overall chronic hyperglycemia [98][99][100][101] .…”
Section: Glycosylated Haemoglobin: the Evaluation Of Glycosylated Hb mentioning
confidence: 99%
“…Tehran first demonstrated elevation of minor hemoglobin in diabetes mellitus introduced the column method of separating out the fast hemoglobin, pointed out that HbA 1 C is related to control of diabetes. The advantages of Gly Hb estimation are those of a simple procedure, lack of any need for dietary preparation or for fasting, elimination of the variability usually found an oral glucose tolerance tests as well as an accurate reflection of overall chronic hyperglycemia [98][99][100][101] .…”
Section: Glycosylated Haemoglobin: the Evaluation Of Glycosylated Hb mentioning
confidence: 99%
“…Fresh button mushrooms (Agaricus bisporus) treatment with solution of 1.5% CaCl2 + 0.5% citric acid and stored for 16 days at 12°C. The report states that post-harvest chemical treatment maintained better firmness, weight, color and inhibit cellulase, beta-1, 3 glucanase, chitinase and phenylalanine ammonialyase activities [16]. [17] found that CaCl2 treated mushrooms packaged under MAP experienced lowest weight loss and L value (brightness), highest degree of overall color change (ΔE) and glucose contents.…”
Section: Modified Atmosphere Packagingmentioning
confidence: 99%
“…Furthermore, hyperlipidemia may also induce abnormalities like oxidation of lipids, the formation of ketone bodies as well as resistance to insulin in muscle and liver cells in diabetic patients. Treatment of hyperlipidemia with available lipid-lowering drugs: fibrates and bile acid sequestrants are not free from many side effects such as myositis, gastrointestinal upset along with elevated hepatic, renal function tests [11][12][13][14][15][16][17] .…”
mentioning
confidence: 99%